Skin-sparing mastectomy in the UK--a review of current practice. - Sotheran, W. J. (2004)
BACKGROUND: Skin-sparing mastectomy (was first described in 1991 and has achieved popularity because it facilitates immediate breast reconstruction, preserving the infra-mammary fold and breast envelope. Little is known about the use of skin-sparing mastectomy in the UK. METHODS: All members of the BASO Breast Specialty Group were contacted in June 2001 with a questionnaire to determine the popularity of skin-sparing mastectomy, techniques used, indications, contra-indications and outcomes. RESULTS: Of 300 questionnaires sent, 130 were returned by September 2001. The number of respondents using skin-sparing mastectomy increased from 27 (21%) in 1997 to 95 (73%) in 2001. Of respondents, 35 (23%) avoided skin-sparing mastectomy because of their uncertainty about the benefits (22/35), indications (16/35) or oncological safety (13/35). Where skin-sparing mastectomy was performed, it was combined with immediate breast reconstruction in 90% of cases, using latissimus dorsi (84%), subpectoral (70%) or TRAM flap reconstruction (54%). Skin-sparing mastectomy was performed by breast surgeons alone (62%), or with a plastic surgeon (47%) and the preferred incisions were peri-areolar (68%) and elliptical (26%). Most respondents used skin-sparing mastectomy for prophylaxis, in situ cancer and early invasive disease and avoided skin-sparing mastectomy in patients with skin tethering (62%), where radiotherapy was planned (49%) and in smokers (28%). Complications seen by respondents included skin envelope necrosis (68%), haematoma formation (46%), cosmetic failure (41%) and local recurrence (12%). CONCLUSIONS: Skin-sparing mastectomy is becoming popular in the UK, but experience is limited. The variation in indications and techniques indicate the need to establish evidence-based guidelines for the wider practice of skin-sparing mastectomy in the UK.